Performance of first responders in simulated cardiac arrests - Marsch, Stephan; Tschan, Franziska; Semmer, Norbert; Spychiger, Martin; Breuer, Marc; Hunziker, Patrick (My University, 2005)
Objective. Survival of in-hospital cardiac arrests depends more on first responders than on cardiac arrest teams. The objective of this study was to determine the adherence to algorithms of cardiopulmonary resuscitation of first responders in simulated cardiac arrests in intensive care. A second objective was to assess the effect of the early vs. late availability of a physician on the performance of nurse-based teams acting as first responders. Design: Prospective study. Setting. Patient simulator in a tertiary level intensive care unit. Participants: A total of 20 teams consisting of three registered nurses and one resident each. Interventions: A simulated witnessed cardiac arrest due to ventricular fibrillation occurred in the presence of one nurse while the remaining two nurses could be called to help. Depending on the time of the residents' arrival, teams were classified as "early" (median arrival 50 secs after the onset of the arrest) or "late" (median arrival 150 secs after the onset of the arrest). Measurements and Main Results: In all teams, the recognition of the arrest and the calling for help occurred, in a timely fashion. However, a median of 85 secs (interquartile range [10], 130 secs) elapsed until the start of cardiac massage and 100 secs (IQ, 45 secs) to the first defibrillation. Once commenced, cardiac massage and mask ventilation were carried out during 61% (IQ, 33%) and 77% (IQ, 23%) of the possible time only. Delays and interruptions were generally not recalled by the participants. Compared with teams with late arriving residents, teams with early arriving residents administered more countershocks: 4.5 (IQ, 2) vs. 3.5 (IQ, 1.5; p =.026). Conclusions. First responders in intensive care often failed to build a team structure that ensured timely, effective, monitored, and ongoing team activity. The early availability of a physician increased the number of countershocks administered. Self-reporting is unsuitable to reliably assess the quality of cardiopulmonary resuscitation.
Keywords: basic life support; cardiopulmonary resuscitation; intensive care; simulation; patient simulator; witnessed cardiac arrest; CARDIOPULMONARY-RESUSCITATION; VENTRICULAR-FIBRILLATION; PRECORDIAL; COMPRESSION; DEFIBRILLATION; MANAGEMENT; OUTCOMES; ADULTS; TEAMS